Evaluation of a risk score for interhospital transport of critically ill patients. Issue 4 (20th March 2006) - Markakis, C; Dalezios, M; Chatzicostas, C; Chalkiadaki, A; Politi, K; Agouridakis, P J
Abstract : Background: Interhospital transfer imposes essential risk for critically ill patients. The Risk Score for Transport Patients (RSTP) scale can be used as a triage tool for patient severity. Methods: In total, 128 transfers of critically ill patients were classified in two groups of severity according to the RSTP. Statistical analysis was performed using the receiver operating characteristic (ROC) curve and goodness of fit statistics. Results: In total, 66 patients (51.5%) were classified as group I and 62 (48.4%) as group II. Major en route complications were more common in group II patients (19.3% v 3%, p<0.001). Haemodynamic instability was the most common complication. There were significant differences in the mean risk scores between group I and II patients (mean (SD) 4.48 (1.01) v 11.04 (3.47), p<0.001). Discrimination power of RSTP was acceptable (area under the ROC curve 0.743; cutoff value ⩾8). Goodness of fit was adequate (p = 0.390). Conclusion: The RSTP had acceptable discrimination and adequate goodness of fit and could be considered as a triage tool. Haemodynamic instability is the most common problem encountered during transfer.